PERJUANGAN AGRARIA DI KECAMATAN JENGGAWAH KABUPATEN JEMBER: SUATU BENTUK PERLAWANAN SIMBOLIK TAHUN 1998-2005 - badri, mohamad il (P2KK LIPI, 2017)
This paper aims to understand the change of the farmers’ struggle movement from physical into symbolic in a region namely Jenggawah which is located in Jember Regency in 1998-2005. The struggles of the farmers are divided into physical and symbolic struggle. The way of the struggle has changed since 1998. The farmers’ symbolic struggle was conducted through some exhortation and insistence in the form of statement letter for the government or related institution concerning about the land status. Symbolic struggle is an unseen struggle and it can only be recognized through its aim in order to get acknowledgement from other group. The mechanism of this struggle movement tends to be smooth. It is expressed in the form of scientific discourse in written text. The factors that change the movement are the change of political system from New Order Regime into Reformation Era in 1998 and HGU release. The legality of land owning, in the end of this long symbolic struggle, was noted by the gradually launching of land certificates in 2001 from BPN Jember for the farmers. Tulisan ini bertujuan untuk mengetahui perubahan perjuangan agraria di Kecamatan Jenggawah Kabupaten Jember yang merupakan suatu bentuk perlawanan simbolik petani pada tahun 1998-2005. Perlawanan petani Jenggawah terdiri dari dua bentuk, yaitu perlawanan fisik dan perlawanan simbolik. Seiring dengan berjalannya waktu, pola perlawanan petani Jenggawah mengalami perubahan sejak tahun 1998. Perlawanan simbolik petani Jenggawah dilakukan melalui desakan dan paksaan dengan surat pernyataan sikap kepada pemerintah atau lembaga yang terkait mengenai status tanah yang diperjuangkan. Perlawanan simbolik adalah perlawanan tidak tampak dan hanya dikenali dari tujuannya untuk memperoleh pengakuan terhadap kelompok lain. Mekanisme perlawanan simbolik berlangsung secara lembut diekpresikan dalam bentuk wacana ilmiah dalam teks tertulis. Faktor perubahan gerakan dari perlawanan fisik menjadi perlawanan simbolik disebabkan oleh pergantian pemerintahan dari Orde Baru ke Orde Reformasi pada tahun 1998 dan adanya pelepasan tanah HGU untuk diberikan kepada petani. Legalitas pemilikan tanah di akhir perlawanan simbolik ditandai dengan pemberian sertifikat tanah pada tahun 2001 kepada petani Jenggawah oleh BPN Jember secara bertahap.